2008
DOI: 10.1097/hjh.0b013e3282f3b352
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for improved control of hypertension in Taiwan: 1993–2002

Abstract: There was a significant improvement of hypertension awareness, treatment, and control in the TwSHHH survey compared with the NAHSIT survey in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 18 publications
5
65
3
Order By: Relevance
“…17 In particular, the lack of improvement in SBP may prevent the patients to receive the benefits of otherwise improved hypertension care. Compared with the prevalences of hypertension in our study, those reported since 2000 in other studies by age and sex have been lower in most, [18][19][20][21][22][23][24][25][26][27] but not in all populations. 27,28 As in our paper, the rate of awareness of hypertension in these reports was usually more than 60%.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…17 In particular, the lack of improvement in SBP may prevent the patients to receive the benefits of otherwise improved hypertension care. Compared with the prevalences of hypertension in our study, those reported since 2000 in other studies by age and sex have been lower in most, [18][19][20][21][22][23][24][25][26][27] but not in all populations. 27,28 As in our paper, the rate of awareness of hypertension in these reports was usually more than 60%.…”
Section: Discussioncontrasting
confidence: 90%
“…An increasing trend in the prevalence of hypertension was observed in mainland China, in an urban population in Chile 23 in both men and women, and in Taiwan in men. 20 In Taiwan, from the mid-1990s to 2002 and in Chile from 1998 to 2004, the proportions of treatment and control of hypertension have increased, and in their last surveys, these were higher than the proportions in the present paper. These improvements have been attributed to the successful changes regarding the national health-care policy in these countries.…”
Section: Discussioncontrasting
confidence: 50%
“…They were randomly selected from the National Health Interview Survey (NHIS) of Taiwan (2001) conducted by the National Health Research Institutes and Bureau of Health Promotion, Taiwan. 7,8 The NHIS incorporated a multistaged stratified systematic sampling scheme. The 359 township/districts in Taiwan were first grouped into seven strata according to geographic location and degree of urbanization.…”
Section: Methodsmentioning
confidence: 99%
“…There were 3088 male and 3391 female participants aged X19 years old who agreed to participate in the TwSHHH, included in our recent report of hypertension prevalence, awareness, treatment and control in Taiwan. 7 In this study, the analysis of ethnic variation in hypertension prevalence and risk factors in Taiwanese women, only 2810 female TwSHHH participants age at 20-80 years old and whose father and mother had same ethnic background (Minnan, Hakka, Aborigines or Mainland Chinese) were included. Subject's both parents did not have the same ethnicity was excluded in the analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation